The Limitation of Determination Structure of the Agreed Rate of Return for Public-Private Partnership (PPP) Road Projects and Improvement in South Korea - Lee, Hyejin (Archives of Case Reports, 2025)
Public-Private Partnership (PPP) road projects are being promoted worldwide to encourage road investments; however, research on the appropriate rate of return for these projects is insufficient. This is likely because the return on investment for PPP road projects is determined through negotiations between the government and the private sector, a process that remains confidential. The rate of return for PPP road projects is not only a key indicator for evaluating project performance but also a potential driver for future government financial subsidies. Therefore, research on the appropriate rate of return for PPP road projects is necessary for the sustainability of these projects. This study, based on the concept that both the government and the private sector share the anticipated risks of the project, quantifies six types of risks and proposes a model for predicting the appropriate rate of return. The model is able to explain approximately 68% of the cases in South Korea’s PPP road projects. The risk with the greatest influence on the rate of return was found to be an economic risk, while the least influential was regulation change risk. Due to the confidentiality of data related to PPP road projects, this study only utilized 54 cases from South Korea. It is hoped that a wider range of data will be collected and further research on the appropriate rate of return will continue to enhance the sustainability of PPP road projects.